2007
DOI: 10.1177/10598405070230020901
|View full text |Cite
|
Sign up to set email alerts
|

Elementary School Nurse Interventions: Attendance and Health Outcomes

Abstract: Regular school attendance is a necessary part of the learning process; student absenteeism has a direct association with poor academic performance. School nurses can influence student attendance. This study describes the impact of school nurse interventions on student absenteeism and student health. A retrospective review of 240 randomly selected elementary student health folders and attendance records was conducted. School nurses were involved with 75% of high-absence students as compared to 66% of low-absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
(56 reference statements)
0
23
0
Order By: Relevance
“…A growing body of research has examined the effect of school nursing services on students and teachers. On-site school nursing services were effective in improving student health 11 and student attendance, 12,13 reducing early dismissals [14][15][16] and reducing teacher time spent on dealing with student illness or injury. 17,18 However, to our knowledge, no study has assessed the economic impact of school nursing services.…”
mentioning
confidence: 98%
“…A growing body of research has examined the effect of school nursing services on students and teachers. On-site school nursing services were effective in improving student health 11 and student attendance, 12,13 reducing early dismissals [14][15][16] and reducing teacher time spent on dealing with student illness or injury. 17,18 However, to our knowledge, no study has assessed the economic impact of school nursing services.…”
mentioning
confidence: 98%
“…More studies should be performed using loss of seat time as a measure of attendance. Past studies that used conventional attendance data have been unsuccessful because of inconsistency in the collection of this data, high mobility of high‐risk students, and the inability to separate data on nonattendance for health reasons from nonattendance for such other reasons as suspensions and appointments 2,10,22–24 …”
Section: Discussionmentioning
confidence: 99%
“…Weismuller et al [9] described the effect of school nurse interventions on decreasing the rate of student absenteeism because of their increased interaction with students who are absent from school and by giving health guidance to the students. In similar vein [16] found that there is a strong correlation between student attendance (including absenteeism and tardiness) and SBHCs.…”
Section: Presence Of School Nursesmentioning
confidence: 99%
“…Attendance is the number one determinant of the connectedness between students and their school community, whether this is high or low [9]. Since attending school regularly is a necessary part of the learning process, being absent most of the time has a direct negative effect on academic performance [9,10].…”
Section: Absenteeismmentioning
confidence: 99%
See 1 more Smart Citation